Novel cost-effective approach to produce nano-sized contact openings in an aluminum oxide passivation layer up to 30 nm thick for CIGS solar cells. (22nd March 2021) - Kandybka, Iryna; Birant, Gizem; de Wild, Jessica; Buldu, Dilara Gokcen; Kohl, Thierry; Thiruvallur Eachambadi, Ragha; Brammertz, Guy; Manca, Jean V; Meuris, Marc; Poortmans, Jef; Vermang, Bart
Abstract: This work presents a novel method of local contact openings formation in an aluminum oxide (Al2 O3 ) rear surface passivation layer by the selenization of the lithium fluoride (LiF) salt on top of the Al2 O3 for ultra-thin copper indium gallium (di)selenide (CIGS) solar cells (SCs). This study introduces the potentially cost-effective, fast, industrially viable, and environmentally friendly way to create the nano-sized contact openings with the homogeneous distribution in the thick, i.e. up to 30 nm, Al2 O3 passivation layer. The passivation layer is deposited by atomic layer deposition, while the LiF layer is spin-coated. Selenization is done in the H2 Se atmosphere and the optimal process parameters are deduced to obtain nano-sized and uniformly allocated openings as confirmed by scanning electron microscopy images. The contact openings were produced in the different thicknesses of the alumina layer from 6 nm to 30 nm. Furthermore, the Al2 O3 rear surface passivation layer with the contact openings was implemented into ultra-thin CIGS SC design, and one trial set was produced. We demonstrated that the created openings facilitate the effective current collection through the dielectric Al2 O3 layer up to 30 nm thick. However, the upper limit of Al2 O3 thickness in which the contact openings can be created by the described method is not established yet. The produced passivated CIGS SCs show increased external quantum efficiency response due to the optical enhancement of the passivated cells. However, the production of SCs on the Al2 O3 passivation layer with the openings created by selenization of LiF is not optimized yet.